The crusade that's killing prosperity. - Thurow, Lester C. (American Prospect)
The writer contends that the great untold story of the economy in the 1990s is the disguised high rate of unemployment and its direct effect on stagnating living standards. He states that if it is properly counted, the unemployment rate in the U.S. is no better than in Europe and is well into double figures, and he argues that nothing keeps wages from rising as much as a large pool of idle or underemployed workers. He suggests that the current slack labor markets were produced by the war against inflation, which began in the early 1970s and is still ongoing 25 years later. He contends that all of the original reasons for this war are long gone but that, as the war continues, its negative side effects, including falling real wages and rising inequalities, have become far more corrosive than the original reasons for waging the battle against inflation. He suggests that without a reversal in macroeconomic policies, no set of human-capital investment policies, which would be a long-term answer to falling wages, can hope to work.